Evaluation of nutrient loads conveyed to the deep subalpine lakes of Northern Italy through their main tributaries - Dezuanni, Paolo; Copetti, Diego; Dresti, Claudia; Pella, Nicolò; Buzzi, Fabio; Fenocchi, Andrea (Frontiers in Environmental Science, 2025)
Nutrient pollution is a critical issue for lakes, leading to cultural eutrophication, which damages the ecosystem and prevents water uses. Proper watershed management practices must be put into action to effectively oppose eutrophication. Because of the complexities and the multiple layers of stakeholders involved in this process, the only factual way to evaluate improvements in watershed nutrient management is to directly estimate nutrient loads at watershed closing sections through available data from environmental monitoring. The Italian deep subalpine lakes (DSLs: Lake Como, Lake Garda, Lake Idro, Lake Iseo, Lake Maggiore) suffered from extensive eutrophication from the 1950s to the early 1980s. Their water quality improved in the 1980s and 1990s after national regulations were introduced to address nutrient pollution. After the turn of the century, increasingly pressing limits on nutrient disposal have been issued, yet steady if not worsening lake water quality conditions have been observed overall. To shed light on the issue, quantifying present and past external loads to these lakes based on direct measurements is essential. In this work, we focused on the main tributaries of the Italian DSLs, employing the observed time series of flowrate and nutrient concentrations to estimate the loading levels of nitrogen and phosphorus and their temporal evolution over a period ranging between 13 and 42 years according to data availability. The LOAD ESTimator (LOADEST) software was adopted to support the load quantification process. Results show that a general decrease in external nutrient loads is still occurring, albeit at a slow pace, the fastest reduction occurring for the Oglio River flowing into Lake Iseo, which has suffered from severe nutrient pollution till recently. Increasing loads have conversely been identified for the Sarca River flowing into Lake Garda. These outcomes highlight the beneficial actions carried out to reduce nutrient pollution, although a decorrelation analysis between external loads and flowrate is suggested for a clearer evaluation of its evolution across the DSLs.